2013
DOI: 10.1007/s10886-013-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemicals of Pinus halepensis as Drivers of Biodiversity in Mediterranean Open Mosaic Habitats During the Colonization Stage of Secondary Succession

Abstract: The Mediterranean region is recognized as a global biodiversity hotspot. However, over the last 50 years or so, the cessation of traditional farming has given way to strong afforestation at the expense of open habitats. Pinus halepensis Miller, known to synthesize a wide range of secondary metabolites, is a pioneer expansionist species colonizing abandoned agricultural land that present high species richness. Here, laboratory bioassays were used to study the potential impact of P. halepensis on plant diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 50 publications
2
79
0
1
Order By: Relevance
“…We chose to test the effects of natural leachates using leaf aqueous extracts because water-soluble compounds have been shown to be most involved in allelopathy (Fernandez et al, 2013;Gross, 2003).…”
Section: Allelopathic Effects Of Leaf Aqueous Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to test the effects of natural leachates using leaf aqueous extracts because water-soluble compounds have been shown to be most involved in allelopathy (Fernandez et al, 2013;Gross, 2003).…”
Section: Allelopathic Effects Of Leaf Aqueous Extractsmentioning
confidence: 99%
“…Recent studies in France have shown increasing numbers of L. hexapetala fertile populations over the past 15 years Haury et al, 2014;Ruaux, Greulich, Haury, & Berton, 2009), raising concerns about their invasiveness. Indeed, while the majority of studies reports an inhibitory effect of allelochemicals, the allelopathic interactions also include the beneficial influences that a plant could exert over other plants or microorganisms through the release of allelochemicals (Chou, 1999;Fernandez et al, 2013;Rice, 1984). In this case, stimulation of its own seed germination or, conversely, inhibition of L. hexapetala seed germination by the native species mediated by allelochemicals could potentially exert a strong control on the persistence of L. hexapetala populations after disturbances such as managed control efforts (Haury et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The phytotoxic and allelopathic effects of Aleppo pine (Pinus halepensis Miller) have been widely studied from diverse plant organs; the needles include various phenolic and terpenoid compounds (Fernandez et al 2013), which can be autotoxic and thus prevent the germination of seeds in a forest stand (Fernandez et al 2008), as was observed for inhibited Stipa tenacissima grasslands (Navarro-Cano et al 2009). Hamrouni et al (2014) showed allelopathic effects of essential oils of P. halepensis which displayed antifungal and herbicidal activities.…”
Section: Pinusmentioning
confidence: 99%
“…10,15,16 Allelopathic substances with inhibitory activity in plant litter are involved in the competitive ability of host-plants to survive because of their effects on the seed germination, seedling establishment, plant growth, and distribution. 7,[17][18][19] Therefore, HHPEBA may serve for ginkgo survival strategy as an allelopathic active substance that is able to give an advantage in such competition for gingko to survive through the growth inhibition of neighboring plants in the local ecosystems.…”
Section: Figurementioning
confidence: 99%